Comparative efficacy of two ivermectin pour-on anthelmintics in beef steers in a commercial feedyard - Tarpoff, Anthony John (Kansas State University, 2012)
A total of 400 head of naturally parasitized commercial feedyard cattle (subset of 40 hd/pen; 10 pens) were utilized to compare trade name ivermectin pour-on and a generic ivermectin pour-on. The efficacy of each product was measured by obtaining rectal fecal egg counts on day 0 and day 14 using a Modified Wisconsin sugar float with centrifugation from rectal fecal samples and calculating fecal egg reduction post treatment. There were no differences in net egg count reduction between treatments (P= 0.15) at 14 days post-treatment application. Regardless of treatment, only 26% of animals had a fecal egg count reduction of >90% and only 35% achieved a FECR of >80% which is low considering 90% reduction is the accepted efficacy level. Cattle treated with the generic pour-on had improved average daily gains (ADG) compared to cattle treated with the trade name pour-on P = 0.02. This study demonstrated decreased efficacy of both products with a FECR of less than 90% within a commercial feedyard environment.
Keywords: Generic; anthelmintics; Veterinary Medicine (0778)